Users perspective on software piracy in Klang Valley - Sabran, Azri (2003)
Software is a simply define as a set of that cause hardware to do things user want them to do. Today, software has become one of the most precious technologies of the Information Age as in this current time; almost everything from personal computer to the used of Internet needs software. But, new things also bring disadvantages if the technology is not being controlled properly and the advancement of software has created its illegal substitute, pirated software. A research has been conducted under the title of "Users Perspective on Software Piracy in Klang Valley. Its objectives are to determine the extent of use of the software piracy, to identify factors that influencing people in buying and using pirated software, to evaluate the moral and ethical behavior impact of software piracy to users and lastly, to find or suggesting a new ways or possible solution to this problems. The target users under this topic will be selected randomly. This research will consist of 200 samples of respondents. The self-administered questionnaires collected then will be analyzed, coding and cleaning to produce valuable information for this research. Most of the respondents, after research has been done, agreed that they are aware to the Acts, which disallowed pirated software, but they did not really aware about the penalties as to the lack of enforcement done by the authority. Most of them also willing to loose his self-esteem and dignity, in term of this problem, to purchased and use pirated software.